The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1049732318759528
|View full text |Cite
|
Sign up to set email alerts
|

Group Medical Visits as Participatory Care in Community Health Centers

Abstract: In this article, I examine group medical visits, a clinic-based intervention that aims to improve patient health by combining clinical care, health education and peer support. Research shows that health care inequalities are reproduced through the interplay of interpersonal, institutional, and structural factors. I examine changing social relations made possible by group visits, including peer support and an expanded role for patient knowledge. The qualitative data presented here are part of a mixed-methods st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
(58 reference statements)
1
23
0
Order By: Relevance
“…A similar finding was reported in another qualitative study 23 of GMAs in the United States. In addition, Thompson-Lastad 24 reported that staff involved with group medical appointments felt that patient interactions with other patients was the most important aspect of these appointments; they also reported that patients could support one another in ways that health providers could not. Although the social atmosphere may be beneficial for some individuals, in the case of more shy or reserved participants, we found that they had some hesitancy to engage in the conversation and ask questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar finding was reported in another qualitative study 23 of GMAs in the United States. In addition, Thompson-Lastad 24 reported that staff involved with group medical appointments felt that patient interactions with other patients was the most important aspect of these appointments; they also reported that patients could support one another in ways that health providers could not. Although the social atmosphere may be beneficial for some individuals, in the case of more shy or reserved participants, we found that they had some hesitancy to engage in the conversation and ask questions.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although GMAs have shown benefits, understanding patient experiences with these types of appointments is essential to help to refine this emerging approach to care for people with type 2 diabetes. Although a few studies to date have captured qualitative patient experiences and perspectives with this method for managing type 2 diabetes, 7,21,23,24 these type of data are scarce. To our knowledge, no studies have examined naturalistic patient experiences and perspectives of GMAs for type 2 diabetes in a rural Saskatchewan context.…”
Section: Introductionmentioning
confidence: 99%
“…All authors of this article have ongoing qualitative and mixed-methods projects examining group-based integrative care for chronic pain. 14,26,41 Our projects suggest that such approaches are a promising innovation that may help reduce or eliminate opioid medication use while allowing organizations to comply with Joint Commission requirements to offer non-pharmacological chronic pain treatment options. 42 In addition to offering GMVs in which they bill patients' health insurance, most sites offered additional free or low-cost, group-based complementary health approaches such as yoga and tai chi.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative data (reported separately) aimed to provide in-depth understanding of well-developed safety-net IGMV programs. 26 The survey was developed by the authors in consultation with clinicians with IGMV experience. We included questions on the scope and structure of IGMVs around the United States.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding patients’ social context and addressing social determinants of health: In GMVs, patients participate in one another’s care by providing support, resources and advocacy. 6 Extended time and the presence of peers facilitate patients sharing knowledge and experiences, reducing loneliness while providing clinicians, other health care staff and peers the opportunity to provide referrals and follow-up with needed resources. These can include not only access to needed health care (e.g.…”
Section: How Can Gmvs Benefit Clinician Wellbeing?mentioning
confidence: 99%